Mixture of Organophosphates Chronic Exposure and Pancreatic Dysregulations in Two Different Population Samples - Mbah Ntepe Leonel Javeres; Saqlain Raza; Ngondi Judith; Fozia Anwar; Rabia Habib; Sajida Batool; Syed Muhammed Nurulain (Frontiers Media S.A., 2020)
Organophosphates (OP) are a major agrochemical. The application of OP pesticides is expected to increase multifold in the coming decades. The etiology of diabetic diseases is attributed to multiple factors including OP pesticide exposure. The present study investigates pancreatic dysregulation with respect to exocrine enzymes and diabesity in groups of Pakistani and Cameroonian people exposed to a mixture of OP pesticides. Nine hundred and four OP exposed individuals were enrolled for this cross-sectional study after due consent and approval from an ethical review committee. Pesticides' residues were measured by GC-MS spectrometry. Cholinergic enzymes were measured by Elman's method. Serum glucose, insulin, serum amylase, lipase, and triglyceride were measured by spectrophotometry and ELISA; HOMA-IR was determined in OP exposed and non-exposed participants. Stata 15 and R 3.2.0 software were used for statistical analysis of the data. Malathion, chlorpyrifos, and parathion residues were evident in plasma samples. RBC-acetylcholinesterase was significantly depressed in OP exposed groups. In both population samples, investigated pancreatic functions were found to be statistically significantly more dysregulated than non-exposed. OP exposure indicated risk of diabetes and insulin, glycaemia, adiponectin, triglycerides, and TNF-α dysregulations. The study concludes that both OP exposed population groups exhibited a mixture of OP residues and pancreatic dysregulation, although the effect was more pronounced in the Cameroonian population. In addition, serum lipase has a positive correlation with OP exposure and diabetes and may be suggested as an alternate/additional diagnostic marker for diabesity under OP exposure. However, screening of other environmental co-factors with OP for pancreatic dysregulation is suggested.